Utilization of kepok banana flour and tempeh flour in making flakes - Yossie Kharisma Dewi; Theresia Meilaxty Rumapea; Usman Pato; EVY ROSSI (AGROINTEK, 2023)
Utilization of banana flour in making flakes is one of the efforts to diversify flakes products. Flakes made from kepok banana flour have a high carbohydrate but low protein content. According to SNI, the minimum requirement for protein in cereal products is 5%, so to meet the protein content in flakes, it needs to be combined with other ingredients, such as tempeh flour. The use of tempe flour in making flakes made from kepok banana flour is expected to increase the protein content of flakes. This research aimed to determine and obtain the best ratio between kepok banana flour and tempeh flour for making flakes. This research used a completely randomized design with four treatments and four replications. The treatments in this research were the difference in the ratio between kepok banana flour and tempeh flour, namely PT0 (kepok banana flour 100%), PT1 (90:10), PT2 (80:20), and PT3 (70:30). Data were analyzed using variance analysis and then continued with Duncan's New Multiple Range Test at 5% level. The result showed that the ratio of kepok banana flour and tempeh flour significantly affected moisture, ash, fat, protein, crude fiber, carbohydrate contents, crispy resistance in milk, and descriptive and hedonic sensory test. The best ratio of kepok banana flour and tempeh flour was 70:30, respectively. It had 1.77% moisture, 3.39% ash, 11.40% fat, 9,23% protein, 5.52% crude fiber, 74.22% carbohydrate, and crispy resistance in milk 7,61 minutes with a description of light brown, banana and tempeh flavored, crunchy texture, and banana and tempeh taste. Panelists preferred a hedonic assessment of color, aroma, taste, and overall assessment, and panelists preferred the crunchy texture